Asuhan Kebidanan Komprehensif Pada Ny “ R “ Umur 26 Tahun 38 Minggu Dengan Kekurangan Energi Kronik (Kek) - Riski, Merisa; S, Susilawati; Ariyani, Yulinda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Lack of maternal knowledge about Chronic Energy Deficiency is one of the indirect causes of maternal and infant mortality. Comprehensive Midwifery Care is one way to reduce MMR and IMR, especially those that occur in PMB Hj.SRI NIRMALA. The purpose of this Final Assignment Report is to provide comprehensive care for pregnant women, childbirth, newborns, postpartum period, and family planning with the SOAP method. Comprehensive midwifery care is carried out at PMB Hj.Sri Nirmala starting from the third trimester of pregnancy, childbirth, BBL, postpartum period and family planning. Care began on February 8 to April 6, 2024. This comprehensive midwifery care was carried out on Mrs. R, 26 years old G2P1A0 at 36 weeks of pregnancy at PMB Hj.Sri Nirmala. There were 2 pregnancy visits, 1 delivery, 4 postpartum visits, 3 BBL visits, and 1 family planning visit. During pregnancy, the mother did not have any complaints and the examination results were normal. On February 25, 2024, the mother reported signs of labor at 40 weeks and 2 days gestation. The labor process proceeded normally at PMB Hj. Sri Nirmala, with the first stage lasting 6 hours, the second stage lasting 20 minutes, the third stage lasting 10 minutes, and the fourth stage lasting 2 hours. Postpartum and newborn visits showed normal maternal and infant health. At the 6-week visit, the mother had received a 3-month contraceptive injection. With comprehensive midwifery care and IEC, it is hoped that the client will implement it so that the mother and baby remain healthy, thereby reducing maternal and infant mortality